Online liquor gets audited: a review of regulatory controls and supply practices of online liquor retailers in NSW, Australia - Jonathon Noyes; Melissa Palermo; Arlita Willman |; Jenna Harkness; Rachel Bienenstock; Paul Klarenaar (Public Health Research & Practice, 2022)
Objectives: In New South Wales (NSW), Australia, the number of ‘online liquor licences’ – packaged liquor licences with conditions restricting the sale of alcohol to online, phone or fax orders – increased from 101 in 2010 to 500 by May 2018. International and national evidence is emerging that this growth in online liquor licences has been accompanied by increased risk of supply to young and intoxicated people. This study aimed to determine the extent to which online liquor retailers in NSW have adopted safeguards to prevent people younger than 18 years purchasing alcohol online; and the supply of alcohol to intoxicated people. It also aimed to assess the regulatory framework in NSW for these licences.